2013
DOI: 10.2478/pomr-2013-0032
|View full text |Cite
|
Sign up to set email alerts
|

An Ant Colony Algorithm for efficient ship routing

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Different swarm intelligence methods have been used in various scenarios. For example, Kosmas and Vlachos (2012) used simulated annealing, whereas Tsou and Cheng (2013) proposed ant colony optimization for this task. A number of studies have demonstrated the usage of evolutionary algorithms in different configurations, such as multi-objective evolutionary algorithm (Marie and Courteille 2009;Szłapczynska and Smierzchalski 2009;Vettor and Soares 2016), or realcoded genetic algorithm (Maki et al 2011;Wang et al 2018).…”
Section: Related Workmentioning
confidence: 99%
“…Different swarm intelligence methods have been used in various scenarios. For example, Kosmas and Vlachos (2012) used simulated annealing, whereas Tsou and Cheng (2013) proposed ant colony optimization for this task. A number of studies have demonstrated the usage of evolutionary algorithms in different configurations, such as multi-objective evolutionary algorithm (Marie and Courteille 2009;Szłapczynska and Smierzchalski 2009;Vettor and Soares 2016), or realcoded genetic algorithm (Maki et al 2011;Wang et al 2018).…”
Section: Related Workmentioning
confidence: 99%
“…When V w is greater than the critical STW, the ship must be slowed down, which is known as the voluntary speed reduction. In this paper, the following equations are used to calculate the critical STW [50,51]:…”
Section: The Speed Correction Modelmentioning
confidence: 99%
“…In addition to the above methods, some evolutionary heuristic algorithms have been used to solve the ship weather routing problem in recent years, such as the simulated annealing algorithm (Kosmas and Vlachos, 2012), ant colony algorithm (Tsou and Cheng, 2013), genetic algorithm (Maki et al, 2011; Kang et al, 2012), and multi-objective evolutionary algorithm (Marie and Courteille, 2009; Szłapczyńska and Śmierzchalski, 2009; Szlapczynska, 2015; Vettor and Soares, 2016).…”
Section: Summary Of Previous Workmentioning
confidence: 99%